2013
DOI: 10.1021/ja4014375
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Hydrophobic Protein–Carbohydrate Interactions to Fine-Tune Monoclonal Antibodies

Abstract: Biologically active conformations of the IgG1 Fc homodimer are maintained by multiple hydrophobic interactions between the protein surface and the N-glycan. The Fc glycan modulates biological effector functions, including antibody-dependent cellular cytotoxicity (ADCC) which is mediated in part through the activatory Fc receptor, FcγRIIIA. Consistent with previous reports, we found that site-directed mutations disrupting the protein–carbohydrate interface (F241A, F243A, V262E, and V264E) increased galactosylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
114
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(126 citation statements)
references
References 67 publications
11
114
0
Order By: Relevance
“…This switch in receptor specificity coincides with a switch in effector function in vivo, as sialylated IgG suppresses inflammation in mouse models of autoimmunity. Recent structural data support an earlier computational model that sialylation increases the conformational flexibility of the C H 2 domain, sampling conformations compatible with type II FcR binding (8,20,36).…”
Section: Discussionsupporting
confidence: 62%
“…This switch in receptor specificity coincides with a switch in effector function in vivo, as sialylated IgG suppresses inflammation in mouse models of autoimmunity. Recent structural data support an earlier computational model that sialylation increases the conformational flexibility of the C H 2 domain, sampling conformations compatible with type II FcR binding (8,20,36).…”
Section: Discussionsupporting
confidence: 62%
“…In this case, we identified GnT1 activity as being modulated, showing that not only trimming, but also the initial part of the elongation is affected by surface glycan interaction, in line with other reports that suggested the effect of N-glycan-carbohydrate interaction on glycan processing and protein structure (44,45,50). For example, studies performed on antibodies showed the role of a phenylalanine on the IgG glycan distribution by modifying the protein stability (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…6,19,20 The impact of the presence of terminal sialic acid residues is also uncertain. [21][22][23][24][25][26][27][28][29][30] Indeed, the discrepancies in the methods used for evaluating biological activity, the variability in the type and level of sialylation, as well as the lack of a systematic in-depth glycan characterization, all contribute to the ambiguity of its role in IgG functions. In humans, sialic acids can be attached to the Fc-glycans either on the C3-or the C6-hydroxyl group of the terminal galactose, through the action of a2,3-sialyltransferases (ST3) or the a2,6-sialyltransferase-1 (ST6).…”
Section: Introductionmentioning
confidence: 99%
“…22 Contradictory results were also reported on sialylated Fcs' ability to bind FcgRIIIa, but using dissimilar IgG preparations and affinity measurement protocols. 21,28 In other studies assessing the anti-inflammatory properties of a2,6-sialylated IgGs, 21,24,26,30 blood-derived or recombinant antibodies were enriched by affinity chromatography using Sambucus Nigra agglutinin-resins that were shown to catch mainly IgGs bearing Fab-sialylated glycans to the detriment of Fc-sialylated species. 24,32,37 While the specific involvement of Fc's a2,6-sialylation in anti-inflammatory activity was shown by Anthony et al in their model, 35 which receptor the sialylated Fcs are targeting remains controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation